A Framework for Seismic Design of Items in Safety-Critical Facilities for Implementing a Risk-Informed Defense-in-Depth-Based Concept - Itoi, Tatsuya; Iita, Yuki; Sekimura, Naoto (Frontiers in Built Environment, 2017)
Recently, especially after the 2011 off the Pacific coast of Tohoku Earthquake and the Fukushima Daiichi Nuclear Power Plant accident, the need for treating residual risks and cliff edge effects in safety-critical facilities has been widely recognized as an extremely important issue. In this paper, the sophistication of seismic designs in safety-critical facilities is discussed from the viewpoint of mitigating the consequences of accidents, such as the avoidance of cliff edge effects. For that purpose, the implementation of a risk-informed defence-in-depth-based framework is proposed in this study. A basic framework that utilises diversity in the dynamic characteristics of items and also provides additional seismic margin to items important for safety when needed is proposed to prevent common cause failure and to avoid cliff edge effects as far as practicable. The proposed method is demonstrated to be effective using an example calculation.